Impacts of Triclosan in Greywater on Soil Microorganisms - Danielle I. Harrow; Jill M. Felker; Katherine H. Baker (Applied and Environmental Soil Science)
The use of greywater for irrigation is becoming a common practice in arid regions such as the Southwestern US, the Middle East, Australia, and China. While greywater supplies nutrients to soil ecosystems, the possible impact of trace contaminants, particularly pharmaceuticals and personal care products, has not been determined. This paper examined the impact of triclosan, an antibacterial agent commonly added to consumer products, on microbial populations and microbial diversity in soil irrigated with greywater. While there was no change in the total number of heterotrophic microorganisms in the soil, both the types and the antibiotic resistance of the microorganisms were significantly influenced by triclosan. The proportion of the microbial isolates resistant to antibiotics increased while at the same time, overall diversity of the microbial community decreased.